Experimental and simulation-based comparative analysis of different parameters of PV module - Koondhar, Mohsin Ali; Laghari, Imtiaz Ali; Asfaw, Belay Million; Reji Kumar, Rajamony; Lenin, A. Haiter (Elsevier B.V., 2022)
enewable Energy (RE) has been rapidly growing day by day as a need of the world due to the energy crises and environmental effects. In recent years, the use of solar systems for the generation of electricity has gained considerable popularity. This increase mainly results from a scarcity of other energy sources, such as fossil fuels. As a result, there is a pressing need to transition to more dependable and long-term resources, such as photovoltaic (PV) systems. To improve the performance of PV proper design and development have been required for adequate extraction of their essential parameters. This study proposed the implementation and behaviour of a photovoltaic module (PVM) and describes the individual main equation situated on the Shockley diode to enable a detailed study of semiconductor physics and PV occurrence. The environmental performance of a PVM is represented using MATLAB which can be illustrative of the PVM for simple use in the simulation phase. The model was designed in MATLAB, an easy-to-use icon and dialog box that depends on the effect of solar radiation (SR) and cell temperature, output current (I) versus (vs) voltage (V), and power vs. Voltage. PVM is made with the simulated models are simulated and optimized. These models have been used to analyze the outcome of variations in various specifications on the PVM, including the operating temperature and the level of SR. The observed results have been compared with outcomes characteristics of PV, which are specified on the technical datasheet of the PVM. Simulation results have been obtained by using MATLAB software. From the results, it can be seen that at insolation 900W/m2 the output power of PVM is 280 but at 10°C the power of PVM is 270.